Rodowa uprawa zachowawcza jodły pospolitej z rezerwatu „Tisovik” w Puszczy Białowieskiej - Korczyk, Adolf (Leśne Prace Badawcze, 2026)
The “Tisovik” reserve, located in the Belarusian part of the Białowieża Forest, holds an isolated relic stand of silver fir, situated 120 km to the north-east of the main forest. In order to preserve this relic fir stand, a ancestral conservative tillage consisting of the Jd 92 trial (plot I) and the Jd 94 trial (plots II and III) was established between 1992 and 1994 in the Polish part of the Białowieża Forest on the territory of the Hajnówka Forest District. The growth and development of the progeny of 20 firs were characterized by means of long-term observations made in these trials. In 2000 (at the age of 18), the firs in the Jd 92 trial (plot I) reached an average height of 394.86 cm with a mean diameter at breast height of 42.42 mm and the average rate of survival amounted to 75%. In the Jd 94 trial, the rate of fir survival on plot II was 70% (at the age of 15) with an average height of 277.08 cm and a diameter at breast height of 36.62 mm, while on plot III only 50 trees with an average height of 198.6 cm and a diameter at breast height of 24.49 mm survived. The results of this study show that the fir progeny in the “Tisovik” reserve is of high breeding value. Therefore, the silver fir seed stock of the “Tisovik” reserve is suitable for the establishment of new plantations in the Polish part of the Białowieża Forest and the Mazury-Podlasie Region.